PERSPEKTIF PERTANGGUNGJAWABAN NEGARA ATAS PENEGAKAN HUKUM LINGKUNGAN HIDUP DI INDONESIA - Muhammad Syaiful Anwar; Rafiqa Sari (Fakultas Hukum Universitas Bangka Belitung, 2021)
Environmental law enforcement put forward settlement of dispute through administration law as well as civil and criminal law. Based on the principle of state responsibility, the state will guarantee that the utilization of natural resources will provide benefits for the greater well-being and quality of life, both present and future generations as a goal of the implementation of sustainable development.The formulation of the problem a point issue is environmental management in Indonesia by the state in accordance with the principle of state responsibility? And, how is the implementation of sanctions as environmental law enforcement based on Government Regulation of the Republic of Indonesia Number 22 of 2021 concerning the Implementation of Environmental Protection and Management? The method used in this research is juridical normative with regulation approach. The results of the study conclude that Indonesia has not been maximized in carrying out the function of the principle of state responsibility because there is still a lot of forest destruction that has occurred, and law enforcement, both administrative, civil and criminal, should be carried out in a balanced manner so that the deterrent effect of law enforcement can be a reflection for the parties who will do environmental damage